2018
DOI: 10.1538/expanim.18-0062
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation-mediated genome editing in vitrified/warmed mouse zygotes created by IVF via ultra-superovulation

Abstract: Recently, genome editing in mouse zygotes has become convenient and scalable, in association with various technological developments and improvements such as novel nuclease tools, alternative delivery methods, and contemporary reproductive engineering techniques. We have so far demonstrated the applicability of ultra-superovulation, in vitro fertilization (IVF), and vitrification/warming of zygotes in microinjection-mediated mouse genome editing. Moreover, an electroporation-mediated method has rapidly become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Vitrification has become more and more popular in conservation of mammalian embryos because of its simplicity, speed, low cost, and high success rate. To date, vitrification of embryos in cattle (Taylor-Robinson et al, 2014 ), mouse (Nakagawa et al, 2018 ), and human (Wei et al, 2019 ) is becoming a routine procedure in facilitating the wide application of assisted reproductive technologies in these species. However, vitrification of porcine embryos still remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Vitrification has become more and more popular in conservation of mammalian embryos because of its simplicity, speed, low cost, and high success rate. To date, vitrification of embryos in cattle (Taylor-Robinson et al, 2014 ), mouse (Nakagawa et al, 2018 ), and human (Wei et al, 2019 ) is becoming a routine procedure in facilitating the wide application of assisted reproductive technologies in these species. However, vitrification of porcine embryos still remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, IASe-derived fertilized oocytes at the pronuclear stage are used in gene modification through microinjection or electroporation. 3133 In this study, we demonstrated that our optimized superovulation protocol for NOG mice was effective in efficiently and promptly expanding a colony of genetically engineered NOG mice. Additionally, an efficient production and storage system of NOG mice was developed through embryo and sperm cryopreservation.…”
Section: Discussionmentioning
confidence: 76%
“…In some studies, electroporation was done in mouse zygotes that were denuded of the zona pellucida (ZP) by a Tyrod's acid treatment (Qin et al, 2015;Chen et al, 2016;Wang et al, 2016), without affecting the early development unlike data reported in rats (Okuyama and Funahashi, 2012). Electroporation also can be applied to mouse and rat frozen zygotes for efficient introduction of CRISPR RNP complexes, without affecting embryo viability or development (Nakagawa et al, 2018;Kaneko and Nakagawa, 2020).…”
Section: Electroporationmentioning
confidence: 99%